Implementation of New Technique for Phyto- and Chemical Melioration of Acidic and Saline Soils - Zaimenko, N.V.; Didyk, N.P.; Ellanska, N.E.; Ivanytska, B.O.; Pavluchenko, N.A.; Rakhmetov, D.B.; Kharytonova, I.P. (Science and Innovation, 2024)
The advanced technique for the reclamation of acidic and saline soils based on the integrated use of siliceous compounds for joint cultivation of cereals, legumes, and cruciferous plants has been implemented. Procedure for the use of chemical and phyto- ameliorants in different soil and climatic zones of Ukraine has been designed. The siliceous mixes with high ameliorative potential and optimal dosages for their application have been identified. Chemical and phyto- ameliorants have been comprehensively studied; their role in stimulation of the development of agriculturally useful microbiota has been determined, Agrophysical, agrochemical, and biological characteristics of soil have been improved, with toxicity and soil sickness reduced due to the use of siliceous mixes. The structure of crop rotation has been improved.